PREPARASI KATALIS NIKEL-ARANG AKTIF UNTUK REAKSI HIDROGENASI ASAM LEMAK TIDAK JENUH DALAM MINYAK KELAPA - Imam Rasidi; Anak Agung Bawa Putra; I Wayan Suarsa (Jurnal Kimia (Journal of Chemistry), 2015)
This study aims to determine the optimum concentration of nickel nitrate in the formation of a nickel catalyst  embedded on activated charcoal by impregnation method, the chemical and physical properties of nickel- coconut shell charcoal in partidular acidity and surface area, as well as the ability of nickel-charcoal catalyst activity in the hydrogenation of linoleic methyl ester in coconut oil. The study begins with a preparation of a mixture of activated charcoal with NaOH activation and preparation of nickel-activated charcoal catalyst with a wet impregnation method. At this stage FT-IR and UV-Vis were used to characterize the products. The resulting catalytic activity was tested with the hydrogenation reaction. Esterification was then performed and the result was determined with GC-MS. The optimum concentration of the catalyst was found to be 0,3M. The catalyst acidity was indicated by the presence of oxide groups including carboxyl, phenols, aldehydes and carbonyl groups, whereas the average surface area was about 21.8753 m2/g. The catalytic activity of nickel-activated carbon in the hydrogenation reaction of methyl ester was optimum at a pressure of 2 atmospheres.